ANALISIS MANAJEMEN PENGELOLAAN OBJEK WISATA CANDI PULAU SAWAH MENURUT ETIKA BISNIS ISLAM - Kelvin Ariansyah; Zuwardi (Jurnal Ekonomi dan Bisnis, 2025)
This research is motivated by analyzing the management of the Sawah Island Temple tourist attraction from the perspective of Islamic business ethics. Sawah Island Temple, as an important historical site, offers significant economic and educational opportunities for local communities and visitors. However, management that does not pay attention to ethical principles can give rise to various problems, such as degradation of historical and environmental values and social injustice. The aim of this research is to determine efforts to manage the Sawah Island temple tourist attraction by applying the values of Islamic business ethics. To find out the obstacles that exist in the application of Islamic business ethics values in managing the Sawah Island temple tourist attraction. The type of research used in this research is field research with a descriptive qualitative approach. The results of this research show that the management of the Sawah Island Temple tourist attraction uses the POAC (Planning, Organizing, Actuating, Controlling) approach. In the planning aspect, there is a need to improve long-term planning and development of tourist attractions. The organizing aspect shows that there are overlapping tasks and a lack of coordination between members. In the implementation (Actuating) aspect, it was found that staff motivation was still low due to lack of incentives and training. The monitoring aspect (Controlling) reveals that the existing evaluation and supervision mechanisms have not been running optimally. In reviewing Islamic business ethics based on 5 principles including Unity, Equilibrium, Free Will, Responsibility and Benevolence, the management of the Sawah Island Temple tourist attraction is not fully in accordance with Islamic business ethics. This management analysis is not in accordance with the principles of Unity (divinity), Equilibrium (balance), free will (free will). Management analysis that is appropriate is only Responsibility (responsibility) and benevolence (honesty).